Kumon Tuition Student Information Management and Academic Monitoring System with Secure Access Control and Data Privacy - Mohd Puad, Fatin Aqilah; Abdullah, Zubaile (Applied Information Technology And Computer Science, 2025)
The Kumon Tuition Student Information Management and Academic Monitoring System with Secure Access Control and Data privacy aims to develop an information management system for students that includes academic tracking with security features. The current non-existing system results in disorganization and inefficiency in managing student data. Additionally, sensitive student data remains unprotected due to the absence of an existing system. The system implements security mechanisms such as two-factor authentication (2FA) using one-time password (OTP), Bcrypt for password hashing, role-based access control (RBAC) and reCAPTCHA. Agile methodology was used to ensure flexible and efficient development. The method of securing sensitive information and managing data interactions is applied in web-based academic platform. The system is expected to address challenges in managing student data and protecting sensitive information, while providing key benefits such as reliability, efficiency, user-friendliness and security.